Characterization of allergenicity of Platanus pollen allergen a 3 (Pla a 3) after exposure to NO2 and O3. (1st June 2021) - Zhou, Shumin; Wang, Xingzi; Lu, Senlin; Yao, Chuanhe; Zhang, Luying; Rao, Lanfang; Liu, Xinchun; Zhang, Wei; Li, Shuijun; Wang, Weiqian; Wang, Qingyue
Abstract: Pollen allergens, widely present in the atmosphere, are the main cause of seasonal respiratory diseases that affect millions of people worldwide. Although previous studies have reported that nitrogen dioxide (NO2 ) and ozone (O3 ) promote pollen allergy, the specific biological processes and underlying mechanisms remain less understood. In this study, Platanus pollen grains were exposed to gaseous pollutants (NO2 and O3 ). We employed environmental electron microscopy, flow cytometry, western blot assay, enzyme-linked immunoassay, ultraviolet absorption spectrometry, circular dichroism, and protein mass spectrometry to characterise the subpollen particles (SPPs) released from pollen grains. Furthermore, we determined the immunogenicity and pathogenicity induced by Platanus pollen allergen a 3 (Pla a 3). Our results demonstrated that NO2 and O3 could damage the pollen cell membranes in SPPs and increase the amount of Pla a 3 allergen released into the atmosphere. Additionally, NO2 and O3 altered the structure of Pla a3 protein through nitrification and oxidation, which not only enhanced the immunogenicity of allergens but also increased the stability of the protein. In vivo analysis using an animal model indicated that NO2 and O3 greatly aggravated pollen-induced pneumonia. Thus, our study provides guidance for the prevention of pollen allergic diseases. Graphical abstract: Image 1 Highlights: Allergenic protein (including Pla a3) found in subpollen particles (SPPs). NO2 and O3 could damage the pollen cell membrane. NO2 and O3 could change the structure of Pla a3 protein and aggravate pollen allergic reaction.